A systematic review on the use of virtual reality in post-stroke patients: exploring when modalities make the difference in executive and motor recovery - Cardile, Davide; Arena, Chiara; Corallo, Francesco; Giuffrida, Giulia Maria; Giustiniani, Andreina; Maggio, Maria Grazia; Rifici, Carmela; Quartarone, Angelo; Tomaiuolo, Francesco; Calabrò, Rocco Salvatore (Frontiers in Virtual Reality, 2025)
BackgroundVirtual reality (VR) has emerged as a promising tool in post-stroke neurorehabilitation, offering immersive and interactive environments capable of enhancing motor and executive function recovery through mechanisms of neuroplasticity. Although various VR modalities—immersive (I), semi-immersive (SI), non-immersive (NI), and mixed (MXD)—have been applied, their relative effectiveness remains unclear.ObjectiveThis systematic review aimed to evaluate the efficacy of different VR modalities in improving motor or executive functions in post-stroke patients and to explore how the stroke phase and the type of VR system used influence treatment outcomes.MethodsA comprehensive literature search was conducted across PubMed, Embase, Scopus, and the Cochrane Library, resulting in 46 eligible peer-reviewed studies published between 2014 and 2024. These studies included randomized controlled trials, quasi-experimental designs, and observational studies, with an average sample size of approximately 35 participants. The inclusion criteria focused on studies utilizing VR as a therapeutic modality for motor or executive function recovery in post-stroke populations.ResultsForty-six studies met the inclusion criteria. Overall, VR interventions yielded positive motor outcomes in 76.3% of cases, with semi-immersive VR (SI-VR) achieving the highest proportion of significant improvements (88.24%), followed by non-immersive VR (NI-VR) (66.67%) and immersive VR (I-VR) (50%). Only 13% of studies assessed executive functions, but SI-VR and I-VR modalities showed more consistent benefits than NI-VR. No statistically significant associations were found between VR typology, the stroke phase (chronic vs. subacute), and motor outcome efficacy.ConclusionVR is an effective and versatile adjunct to conventional stroke rehabilitation, with SI-VR showing the most consistent motor benefits and immersive systems offering additional cognitive engagement. The lack of significant differences by stroke phase suggests that VR can be applied across recovery stages. Future research should address the underrepresentation of executive function outcomes and directly compare modalities in well-powered trials.